A review on application of genetic algorithms in cellular manufacturing systems. (22nd February 2022) - Chaudhuri, Barnali; Jana, R.K.; Chattopadhyay, Manojit; Dan, Pranab K.
This study provides a systematic and integrated review of articles, puts into perspective, the conceptualisation and various critical parameters for research on the application of genetic algorithms to cell design of cellular manufacturing systems during the period 1992 to 2015. Taxonomy of genetic algorithms applications in cellular manufacturing systems is suggested by identifying ten objectives/criteria, 33 production factors, and ten performance measures. Considering the heterogeneity of parameters and operators applied by researchers, a metrics for genetic algorithms is developed. The objective of this study is to identify the research trends, chronological progress, the continuous development and the changing pattern of implementation of genetic algorithms in cellular manufacturing systems.